Modeling of a diffusive memristor based on the DT-FNT mechanism transition. (1st September 2022) - Dai, Yuehua; Zou, Jianxun; Feng, Zhe; Li, Xing; Wang, Xu; Hu, Guyue; Zhu, Yunlai; Wu, Zuheng
Abstract: In this work, a compact model of the diffusive memristor is proposed from the perspective of the transition of electronic transmission mechanisms induced by the dynamics of the filament. First, a new physical model is established based on tunneling mechanisms that are used to fit the experimental data, and the results indicate that it is versatile enough for various diffusive memristors. In addition, the threshold voltage ( V th ) of the diffusive memristor negatively correlates with the ratio of ionic migration and the diffusion coefficient ( u i /Ds ), and the hold voltage ( V h ) positively correlates with the ratio of ionic diffusion and the migration coefficient ( Ds/u i ), which is useful for the selection of materials to achieve target electrical properties. Furthermore, the different parameters that influence the simulated switching curve are explored. The results indicate that the desired electrical characteristics can be obtained by adjusting these parameters. A compact electrical module model is then built and tested in LTspice to carry out bio-neuron and bio-synaptic performances completely. These simulations demonstrate that the model is reliable for exploring diffusive memristor applications.